Embracing a Penta helix hub framework for co-creating sustaining and potentially disruptive sterilization innovation that enables artificial intelligence and sustainability: A scoping review - Neil J. Rowan (Science of The Total Environment, 2025)

A review of commercial captive breeding of parrots as a supply‐side intervention to address unsustainable trade - Alisa Davies; Neil D'Cruze; Rowan Martin (Conservation Biology, 2024)
The volume and scale of commercial captive breeding of parrots have grown dramatically in recent decades. Although it has been proposed, and is often assumed, that captive breeding can reduce pressure on wild populations, there has been little scrutiny of the scale, viability, or impacts of captive breeding to prevent overexploitation among parrots, compared with similar approaches in other threatened taxa, such as pangolins or tigers. We reviewed the primary and gray literature to quantitatively and qualitatively evaluate evidence concerning 5 criteria, established a priori, for commercial captive breeding of parrots as an effective supply‐side intervention. We focused on a sample of 16 threatened parrot species that are heavily traded or for which unsustainable trade has been a factor in the decline of wild populations, representing a range of taxonomic groups, life histories, and native regions. We identified multiple major gaps in knowledge of the extent to which these criteria are met, including a lack of quantitative data on breeding productivity under current commercial breeding practices, the scale and scope of commercial breeding practices in growing parrot markets, particularly in the Middle East and Asia, and the lack of financial viability of captive breeding under effective regulation to prevent laundering or use of wild‐sourced specimens as breeding stock. The capacity for captive breeding to displace demand for wild‐sourced parrots varied between species, and complex interactions between trade in different species and contexts sometimes made consequences of commercial production difficult to predict. Decision makers and regulatory authorities should approach commercial captive breeding of parrots with caution and take into account knowledge gaps and cross‐linkages between trade in different species to avoid unanticipated consequences from stimulating and facilitating unsustainable trade in wild‐sourced parrots.

Digital technologies to unlock safe and sustainable opportunities for medical device and healthcare sectors with a focus on the combined use of digital twin and extended reality applications: A review - Neil J. Rowan (Science of The Total Environment, 2024)

Aging of the sea urchin Centrostephanus rodgersii using demi-pyramid microstructure - Craig Blount; Duncan G. Worthington; Maria Byrne; Rowan C. Chick; Neil L. Andrew (Fisheries Research, 2024)

Pulsed ultraviolet (PUV) disinfection of artificially contaminated seawater seeded with high levels of pathogen disease indicators as an alternative for the shellfish industry depuration systems - Gustavo Waltzer Fehrenbach; Emma Murphy; Robert Pogue; Frank Carter; Eoghan Clifford; Ian Major; Neil Rowan (Environmental Science and Pollution Research, 2023)
The increase in pathogen levels in seawater threatens the safety of entire aquatic ecosystems. Foodborne pathogens can potentially accumulate in shellfish, especially in filter feeders such as bivalves, requiring an efficient depuration process before consumption. Alternative approaches to promote a cost-efficient purge at depuration plants are urgently needed. A small prototype pulsed ultraviolet (PUV) light recirculation system was designed, and its depuration potential was tested in a seawater matrix artificially contaminated with high levels of microbial pathogens Escherichia coli , Staphylococcus aureus , Salmonella typhimurium , Bacillus cereus and Candida albicans . The analysis of treatment parameters including voltage, number of pulses and duration of treatment was performed to ensure the highest reduction in contaminant levels. Optimal PUV disinfection was attained at 60 pulses/min at 1 kV for 10 min (a UV output of 12.9 J/cm 2 ). All reductions were statistically significant, and the greatest was observed for S. aureus (5.63 log 10 ), followed by C. albicans (5.15 log 10 ), S. typhimurium (5 log 10 ), B. cereus (4.59 log 10 ) and E. coli (4.55 log 10 ). PUV treatment disrupted the pathogen DNA with the result that S. aureus , C. albicans and S. typhimurium were not detectable by PCR. Regulations were reviewed to address the applicability of PUV treatment as a promising alternative to assist in the reduction of microbial pathogens at depuration plants due to its high efficiency, short treatment period, high UV dose and recirculation system as currently employed in shellfish depuration plants.

Current decontamination challenges and potentially complementary solutions to safeguard the vulnerable seafood industry from recalcitrant human norovirus in live shellfish: Quo Vadis? - Neil J. Rowan (Science of The Total Environment, 2023)

Potential disruptive effects of zoosporic parasites on peatland-based organic freshwater aquaculture: Case study from the Republic of Ireland - Emer A. O'Neill; Neil J. Rowan (Science of The Total Environment, 2023)

Challenges and future opportunities to unlock the critical supply chain of personal and protective equipment (PPE) encompassing decontamination and reuse under emergency use authorization (EUA) conditions during the COVID-19 pandemic: Through a reflective circularity and sustainability lens - Neil J. Rowan (Science of The Total Environment, 2023)

Seafood consumers engagement in reducing environmental impacts from packaging - Cheila Almeida; Jara Laso; David Baptista de Sousa; Ronan Cooney; Paula Quinteiro; Neil Rowan; Ana Cláudia Dias; Eoghan Clifford; Rodrigo G. Reboredo; María Margallo; Maria Leonor Nunes; António Marques (Science of The Total Environment, 2023)

A circular economy framework for seafood waste valorisation to meet challenges and opportunities for intensive production and sustainability - Ronan Cooney; David Baptista de Sousa; Ana Fernández-Ríos; Sinead Mellett; Neil Rowan; Andrew P. Morse; Maria Hayes; Jara Laso; Leticia Regueiro; Alex HL. Wan; Eoghan Clifford (Journal of Cleaner Production, 2023)

Packaging environmental impact on seafood supply chains: A review of life cycle assessment studies - Cheila Almeida; Philippe Loubet; Tamíris Pacheco da Costa; Paula Quinteiro; Jara Laso; David Baptista de Sousa; Ronan Cooney; Sinead Mellett; Guido Sonnemann; Carlos José Rodríguez; Neil Rowan; Eoghan Clifford; et al. (Journal of Industrial Ecology, 2022)
Packaging is fundamental for food preservation and transportation but generates an environmental burden from its production and end‐of‐life management. This review evaluates packaging contribution to the environmental performance of seafood products. Life cycle assessment (LCA) studies were evaluated by both qualitative and quantitative analysis. The qualitative analysis assessed how direct (e.g., packaging material) and indirect impacts (e.g., influence on seafood loss and waste) have been considered, while the quantitative analysis evaluated packaging contribution to products’ weight and climate change impact. Qualitative analysis revealed that seafood LCAs focus mainly on direct environmental impacts arising from packaging materials, for which some articles conducted sensitivity analysis to assess materials substitution. Recycling was found to be the most common recommendation to diminish direct potential environmental impacts arising from packaging end‐of‐life. However, standardized recovery rates and other end‐of‐life options (e.g., reuse), should be considered. Quantitative analysis revealed that cans' production contributes significantly to the overall climate change impact for canned products. On average, it contributes to 42% of a product's climate change impact and 27% of a product's weight. Packaging has a lower contribution when considering freezing, chilling, and other post‐harvesting processing. It represents on average less than 5% of a product's climate change impact (less than 1 kg CO 2 eq/kg) and 6% of a product's weight. Packaging material production is more relevant to aluminum, tinplate, and glass than for plastic and paper. Therefore, it is essential to accurately include these materials and their associated processes in inventories to improve the environmental assessment of seafood products.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Multi‐century trends to wetter winters and drier summers in the England and Wales precipitation series explained by observational and sampling bias in early records - Conor Murphy; Robert L. Wilby; Tom K. R. Matthews; Peter Thorne; Ciaran Broderick; Rowan Fealy; Julia Hall; Shaun Harrigan; Phil Jones; Gerard McCarthy; Neil MacDonald; Simon Noone; et al. (International Journal of Climatology, 2020)
Globally, few precipitation records extend to the 18th century. The England Wales Precipitation (EWP) series is a notable exception with continuous monthly records from 1766. EWP has found widespread use across diverse fields of research including trend detection, evaluation of climate model simulations, as a proxy for mid‐latitude atmospheric circulation, a predictor in long‐term European gridded precipitation data sets, the assessment of drought and extremes, tree‐ring reconstructions and as a benchmark for other regional series. A key finding from EWP has been the multi‐centennial trends towards wetter winters and drier summers. We statistically reconstruct seasonal EWP using independent, quality‐assured temperature, pressure and circulation indices. Using a sleet and snow series for the UK derived by Profs. Gordon Manley and Elizabeth Shaw to examine winter reconstructions, we show that precipitation totals for pre‐1870 winters are likely biased low due to gauge under‐catch of snowfall and a higher incidence of snowfall during this period. When these factors are accounted for in our reconstructions, the observed trend to wetter winters in EWP is no longer evident. For summer, we find that pre‐1820 precipitation totals are too high, likely due to decreasing network density and less certain data at key stations. A significant trend to drier summers is not robustly present in our reconstructions of the EWP series. While our findings are more certain for winter than summer, we highlight (a) that extreme caution should be exercised when using EWP to make inferences about multi‐centennial trends, and; (b) that assessments of 18th and 19th Century winter precipitation should be aware of potential snow biases in early records. Our findings underline the importance of continual re‐appraisal of established long‐term climate data sets as new evidence becomes available. It is also likely that the identified biases in winter EWP have distorted many other long‐term European precipitation series.

Full Water Quality Monitoring of a Traditional Flow-Through Rainbow Trout Farm - Alexandre Tahar; Alan Kennedy; Richard D. Fitzgerald; Eoghan Clifford; Neil Rowan (Fishes, 2018)
Traditional freshwater rainbow trout farms are still popular in some European countries such as Poland, France and Ireland. These systems generally operate in flow-through configuration. The impact such production systems might have on water quality remains mostly unknown. The present study was set up to fulfil this objective of monitoring water quality on different fish farm locations in order to identify the impacts of the whole farm (comparison of farm inlet and outlet) and at pond scale in order to understand the water quality dynamics and to better understand the impact of multiple water reuse (water passes) in a given pond on water quality. In the absence of any sort of water treatment, an increase in the number of water passes was shown to create an increase in ammonium concentration along the farm. Finally, this traditional flow-through rainbow trout production system was revealed to almost be at its full carrying capacity with respect to internal water quality parameters and fish welfare. To increase fish production, some water treatment techniques (solid/liquid separation, nitrification) would have to be introduced in order to optimize the rearing water quality for fish growth and to minimize the release of pollutants in the receiving water to limit the impact on the environment.

Pulsed light reduces the toxicity of the algal toxin okadaic acid to freshwater crustacean Daphnia pulex - Iain M. T. Murray; Neil J. Rowan; Sara McNamee; Katrina Campbell; Andrew M. Fogarty (Environmental Science and Pollution Research, 2018)

Massive dominance of Epsilonproteobacteria in formation waters from a Canadian oil sands reservoir containing severely biodegraded oil - Casey R. J. Hubert; Thomas B. P. Oldenburg; Milovan Fustic; Neil D. Gray; Stephen R. Larter; Kevin Penn; Arlene K. Rowan; Rekha Seshadri; Angela Sherry; Richard Swainsbury; Gerrit Voordouw; Johanna K. Voordouw; et al. (Environmental Microbiology, 2012)
Summary The subsurface microbiology of an Athabasca oil sands reservoir in western Canada containing severely biodegraded oil was investigated by combining 16S rRNA gene‐ and polar lipid‐based analyses of reservoir formation water with geochemical analyses of the crude oil and formation water. Biomass was filtered from formation water, DNA was extracted using two different methods, and 16S rRNA gene fragments were amplified with several different primer pairs prior to cloning and sequencing or community fingerprinting by denaturing gradient gel electrophoresis (DGGE). Similar results were obtained irrespective of the DNA extraction method or primers used. Archaeal libraries were dominated by Methanomicrobiales (410 of 414 total sequences formed a dominant phylotype affiliated with a Methanoregula sp.), consistent with the proposed dominant role of CO 2 ‐reducing methanogens in crude oil biodegradation. In two bacterial 16S rRNA clone libraries generated with different primer pairs, > 99% and 100% of the sequences were affiliated with Epsilonproteobacteria ( n = 382 and 72 total clones respectively). This massive dominance of Epsilonproteobacteria sequences was again obtained in a third library (99% of sequences; n = 96 clones) using a third universal bacterial primer pair (inosine‐341f and 1492r). Sequencing of bands from DGGE profiles and intact polar lipid analyses were in accordance with the bacterial clone library results. Epsilonproteobacterial OTUs were affiliated with Sulfuricurvum , Arcobacter and Sulfurospirillum spp. detected in other oil field habitats. The dominant organism revealed by the bacterial libraries (87% of all sequences) is a close relative of Sulfuricurvum kujiense – an organism capable of oxidizing reduced sulfur compounds in crude oil. Geochemical analysis of organic extracts from bitumen at different reservoir depths down to the oil water transition zone of these oil sands indicated active biodegradation of dibenzothiophenes, and stable sulfur isotope ratios for elemental sulfur and sulfate in formation waters were indicative of anaerobic oxidation of sulfur compounds. Microbial desulfurization of crude oil may be an important metabolism for Epsilonproteobacteria indigenous to oil reservoirs with elevated sulfur content and may explain their prevalence in formation waters from highly biodegraded petroleum systems.

Medicinal mushrooms: a rapidly developing area of biotechnology for cancer therapy and other bioactivities - John E. Smith; Neil J. Rowan; Richard Sullivan (Biotechnology Letters, 2002)